Process research of grind enriched groats products in the roller machine of the 2-nd grinding system of milling of high-grade flour - Liubych, Vitaliy; Yeremeeva, Olena; Kharchenko, Yevgen (My University, 2023)
The modes of grinding are determined and the mathematical dependences of the product of flour and grain products of the second grinding system with additional equipment entoleiter-dismembler ESM-1,5 are offered. The largest product of flour on the 2nd grinding system is achieved by grinding modes on a roller machine – 35 %. The use of entoleiter-dismembler ECM-1.5 allows to increase the total product of flour on the 2nd grinding system to 62 %.

Встановлені режими подрібнення та математичні залежності борошна та зернових продуктів другої розмелювальної системи із додатковим обладнанням, яким є ентолейтор-дисмембратор ЕСМ-1,5. найбільший вихід борошна на другій розмелювальній системі досягнуто при режимах подрібнення 35 %. Використання ентолейтора-дисмембратора ЕСМ-1,5 дозволяє збільшити загальний вихід борошна на 2-й розмелювальній системі до 62 %.
Keywords: wheat; modes; grinding; flour; systems; пшениця; режими; подрібнення; борошно; системи; кафедра технології зберігання і переробки зерна